FATHER INVOLVEMENT IN EDUCATING EARLY CHILDHOOD CHILDREN IN TERNATE CITY - Puji Dwi Rahayu; Nursin Lidamona (UIN Mataram, 2024)
Abstract The child's growth and development process is strongly influenced by the father's involvement in stimulating, guiding, and educating the child. Father's involvement in raising children is very important. When raising a child, the main attention is given to the mother. The problem is that I don't have much time to educate my children. This study aimed to find out about the father's involvement in educating the child in the City of Ternate from the perspective of father engagement. This research uses descriptive survey research. The data is collected through a manually closed Google form. The data obtained from the research is analyzed descriptively with statistics. Based on the research, fathers play with their children, give them affection, spend time and communicate with them, and interact with them with a score of 49%. Keywords: father's involvement, educating, early childhood. Abstrak Proses pertumbuhan dan perkembangan anak sangat dipengaruhi oleh keterlibatan ayah dalam memberi stimulasi dalam mengasuh, membimbing, dan mendidik anak. Keterlibatan ayah dalam mendidik anak sangat penting. Saat mendidik anak, perhatian terutama diberikan pada ibu. Problemnya adalah ayah tidak memiliki banyak waktu untuk mendidik anak. Tujuan dari penelitian ini adalah untuk mengetahui keterlibatan ayah dalam mendidik anak di Kota Ternate dari perspektif keterlibatan ayah. Penelitian ini menggunakan penelitian survei deskriptif. Data dikumpulkan melalui angket